Ultra-low-angle boundary networks within recrystallizing grains. (October 2017) - Ahl, S.R.; Simons, H.; Zhang, Y.B.; Detlefs, C.; Stöhr, F.; Jakobsen, A.C.; Juul Jensen, D.; Poulsen, H.F.
Abstract: We present direct evidence of a network of well-defined ultra-low-angle boundaries in bulk recrystallizing grains of 99.5% pure aluminium (AA1050) by means of a new, three-dimensional X-ray mapping technique; dark-field X-ray microscopy. These boundaries separate lattice orientation differences on the order of 0.05° and thus subdivide the recrystallizing grain into 2–7 μm wide domains. During further annealing the orientation differences decrease and the overall structure become more uniform while the network remains. It is observed that the morphology of the grain boundaries surrounding the recrystallizing grains relate to the intragranular network and effects hereof on the boundary migration is discussed. Graphical abstract: